Central Effects of Beta-Blockers May Be Due to Nitric Oxide and Hydrogen Peroxide Release Independently of Their Ability to Cross the Blood-Brain Barrier - Laurens, Claire; Abot, Anne; Delarue, Alain; Knauf, Claude (Frontiers in Neuroscience, 2019)
Propranolol is the first-line treatment for infants suffering from infantile hemangioma. Recently, some authors raised the question of potential neurologic side effects of propranolol due to its lipophilic nature and thus its ability to passively cross the blood-brain barrier (BBB) and accumulate into the brain. Hydrophilic betablockers, such as atenolol and nadolol, where therefore introduced in clinical practice. In addition to their classical mode of action in the brain, circulating factors may modulate the release of reactive oxygen/nitrogen species (ROS/RNS) from endothelial cells that compose the BBB without entering the brain. Due to their high capacity to diffuse across membranes, ROS/RNS can reach neurons and modify their activity. The aim of this study was to investigate other mechanisms of actions in which these molecules may display a central effect without actually crossing the BBB. We first performed an oral treatment in mice to measure the accumulation of propranolol, atenolol and nadolol in different brain regions in vivo. We then evaluated the ability of these molecules to induce the release of nitric oxide (NO) and hydrogen peroxide (H2O2) ex vivo in the hypothalamus. As expected, propranolol is able to cross the BBB and is found in brain tissue in higher amounts than atenolol and nadolol. However, all of these beta-blockers are able to induce the secretion of signaling molecules (i.e. NO and/or H2O2) in the hypothalamus, independently of their ability to cross the BBB, deciphering a new potential deleterious impact of hydrophilic beta-blockers in the brain.